'Everyone was questioning everything': understanding the derailing impact of undercover policing on the lives of UK environmentalists. (4th July 2021) - Stephens Griffin, Nathan
ABSTRACT: Between 1968 and 2011, over 150 undercover police officers (spycops) covertly infiltrated more than 1000 political groups in the UK, a large majority of which were left leaning . Undercover officers perpetrated a range of harmful practices including deceiving women into sex; fathering children whilst undercover ; active participation in criminality & acting as agent provocateurs; appearing in court under false identities thus contributing to potential miscarriages of justice, as well as using the identities of dead children without obtaining consent from families. Based on qualitative, biographical interviews with spied-on environmentalists, this article explores the impact of undercover policing on the lives of UK activists. It argues that, in addition to the documented harm and trauma caused by spycops, three further dimensions of impact can be identified. These are ontological uncertainty, whereby activists conceptions of a fixed and stable external reality are fundamentally challenged; derailing, whereby activists were diverted away from environmentalism in a number of different ways both pre and post-exposure of spycops, including diversions into anti-state surveillance activism; and finally, resilience, whereby the agency of activists in the face of egregious human rights abuses is evident. The article argues that the concept of derailing can help to conceptualise the chilling effect of state incursions into activism, whilst also accounting for those who maintained their activism following the revelations.